Rare Combination of Abducens Nerve Palsy and Optic Neuritis on the Same Side: Case Report and Review of 8 Patients in Literature - Toshihiko Matsuo MD, PhD; Daisuke Iguchi MD, PhD (SAGE Publishing, 2024)
The concurrent development of abducens nerve palsy and optic neuritis on the same side is rare. Here we presented an 82-year-old man who developed the combination of abducens nerve palsy and optic neuritis on the left side 2 months after the sixth inoculation of COVID-19 mRNA vaccine. In past history at 45 years old, he experienced subarachnoid hemorrhage and underwent surgery for the clipping of intracranial aneurysm. The patient had no systemic symptoms, such as general fatigue, fever, arthralgia, and skin rashes. Physical and neurological examinations were also unremarkable. Since the aneurysmal metal clip used at that time was not compatible with magnetic resonance imaging, he underwent computed tomographic (CT) scan of the head and showed no space-occupying lesion in the orbit, paranasal sinuses, and brain. As an old lesion, the anterior temporal lobe on the left side had low-density area with metallic artifact on the left side of the skull base, indicative of metal clipping. In 4 weeks of observation from the initial visit, he showed complete recovery of visual acuity and became capable of abducting the left eye in full degrees. We also reviewed 8 patients with the combination of abducens nerve palsy and optic neuritis in the literature to reveal that the combination of signs did occur in mild meningitis with rare infectious diseases and in association with preceding herpes zoster in the first branch of the trigeminal nerve. The course of the present patient suggested that the combination of signs might be vaccine-associated.